Organic Anion Transporting Polypeptide 2B1 (OATP2B1) Genetic Variants: In Vitro Functional Characterization and Association With Circulating Concentrations of Endogenous Substrates - Medwid, Samantha; Price, Hayley R.; Taylor, Daniel P.; Mailloux, Jaymie; Schwarz, Ute I.; Kim, Richard B.; Tirona, Rommel G. (Frontiers in Pharmacology, 2021)
Organic anion transporting polypeptide 2B1 (OATP2B1, gene SLCO2B1) is an uptake transporter that is thought to determine drug disposition and in particular, the oral absorption of medications. At present, the clinical relevance of SLCO2B1 genetic variation on pharmacokinetics is poorly understood. We sought to determine the functional activity of 5 of the most common missense OATP2B1 variants (c.76_84del, c.601G>A, c.917G>A, c.935G>A, and c.1457C>T) and a predicted dysfunctional variant (c.332G>A) in vitro. Furthermore, we measured the basal plasma concentrations of endogenous OATP2B1 substrates, namely estrone sulfate, dehydroepiandrosterone sulfate (DHEAS), pregnenolone sulfate, coproporphyrin I (CPI), and CPIII, and assessed their relationships with SLCO2B1 genotypes in 93 healthy participants. Compared to reference OATP2B1, the transport activities of the c.332G>A, c.601G>A and c.1457C>T variants were reduced among the substrates examined (estrone sulfate, DHEAS, CPI, CPIII and rosuvastatin), although there were substrate-dependent effects. Lower transport function of OATP2B1 variants could be explained by diminished cell surface expression. Other OATP2B1 variants (c.76-84del, c.917G>A and c.935G>A) had similar activity to the reference transporter. In the clinical cohort, the SLCO2B1 c.935G>A allele was associated with both higher plasma CPI (42%) and CPIII (31%) concentrations, while SLCO2B1 c.917G>A was linked to lower plasma CPIII by 28% after accounting for the effects of age, sex, and SLCO1B1 genotypes. No association was observed between SLCO2B1 variant alleles and estrone sulfate or DHEAS plasma concentrations, however 45% higher plasma pregnenolone sulfate level was associated with SLCO2B1 c.1457C>T. Taken together, we found that the impacts of OATP2B1 variants on transport activities in vitro were not fully aligned with their associations to plasma concentrations of endogenous substrates in vivo. Additional studies are required to determine whether circulating endogenous substrates reflect OATP2B1 activity.